TOURISM AS A CROSS-CULTURAL REALITY IN THE MODERN EDUCATIONAL SPACE - H. Fomenko (Academy of Cognitive and Natural Sciences, 2004)
The problems of vocational pedagogies, і e., tourism pedagogics are being dealt with in the frame of tourism logy. The basis categories are separated.